Girls, until a boy says the opposite: language and presence - Catalina Izquierdo; Santiago Rosano (Pontificia Universidad Católica del Perú, 2017)
This work is a reflection on the relationship between the use of language and presence. The guidelines given by the Royal Spanish Academy, which advocates the use of male generically, are questioned. It seems that being a girl is possible  as long as there is not a boy present, at that time her feminine identity is invisible. The rules of the Royal Academy, made from a vision of purely linguistic language, are refuted by several authors who argue that the language has a strong ideological charge. The article gives information about our sexist society, for this reason it defends a language who nomine both sexes, and thus contribute to a culture that values them in the same way; and, therefore, if you opt for a genre in the language, made visible the sex that is marginalized.